RELEVANSI FILSAFAT ISLAM PADA ERA MODERN - Fuad Mahbub Siraj (Jurnal Universitas Paramadina, 2015)
AbstractIslam is a religion that concerned to all aspects of life. Everything has been arranged in accordance with a command from Allah. Religion in Islamic view is a basic principle and a way of life and tawhid is the basis of everything. Islamic philosophy is the result of the entire moslem thought. Islamic philosophy is a religious philosophy, but not ignoring thephilosophical issues. In the perspective of Islamic philosophy nature is not merely a matter without meaning, but signs of the existence of God. Because of that, in Islamic philosophy, when people learn and research nature, they are trying to know their God. Essentially, what is offered by Islamic philosophy is not just a metaphysical aspect – transcendental oriented - normative, without faced to the future, but an attitude ofopenness, rational thinking and sunnah Allāh. Islamic philosophy is necessary to be reconstructed, so this discipline is not rigid. We need the radical efforts to this direction and also the courage to redevelop about what happened and what is practiced by the Islamic philosopher in the past. In other words, it is needed to make a new "ijtihad", because the“ijtihad” of the Islamic philosopher in the past is considered until now as a standard in the Islamic thought. The need of the new ijtihad is the ijtihad that referring to the Islam's mission, to give people a benefit and also suitable to the time condition today, we also do not want to lose the historical continuity of this Islamic philosophy.